The JAK2 V617F point mutation correlates with clinical phenotype in patients with polycythaemia vera and essential thrombocythaemia - Helbig, Grzegorz; Wieczorkiewicz, Agata; Krawczyk, Małgorzata; Kata, Dariusz; Seweryn, Marek; Mendrek, Włodzimierz; Kopera, Małgorzata; Stella-Hołowiecka, Beata; Krzemień, Sławomira (Contemporary Oncology/Współczesna Onkologia, 2008)
Introduction: JAK2V617F, a point mutation involving the JAK2 tyrosine kinase gene, occurs in nearly all patients with polycythaemia vera (PV) and in a variable subset of patients with other myeloproliferative neoplasms (MPN). Aim: We addressed the issue of whe-ther the presence of JAK2 V617F correlates with clinical phenotype. Material and methods: In a single institution study we screened for the JAK2 point mutation in 60 consecutive patients with PV and essential thrombocythaemia (ET). The mutation was detected in peripheral blood granulocyte DNA using allelic discrimination polymerase chain reac-tion (PCR). Results: In total, 42 (70%) patients were positive for this mutation, including 21 subjects with PV (100%), and 21 with TE (54%). The frequency of homozygosity was 21% in PV patients and 0% in ET patients. We found no difference in age at diagnosis, gender or disease duration between patients with and without the mutation. However, a significantly higher haemoglobin concentration and white blood cell count were observed in cases with the JAK2 point mutation. Conversely, the platelet count was significantly lower in V617F-positive cases. Thrombotic complications were more common in patients with V617F. Conclusions: Our results support the previous observation that JAK2 point mutation is associated with some clinical and haematological features in patients with PV and ET.